2021
DOI: 10.22159/ijap.2021.v13s2.20
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Propolis Compounds Potential to Be Covid-19 Therapies by Targeting Sars-Cov-2 Main Protease

Abstract: Objective: The study aims to perform molecular docking to examine the interaction between propolis compound and SARS-CoV-2 main protease. Methods: The protein target of this research was the crystal structure of SARS-CoV-2 main protease in complex with an inhibitor N3 (PDB ID: 6LU7). The ligand of this research was the bioactive compounds from Propolis of Tetragonula aff. biroi. Results: The results showed that propolis compound which has the potential to inhibit SARS-CoV-2 protease activity was S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“… Khayrani et al [8] MLN-4760: –9.2 Sulabiroins A (–9.5), sulabiroins B (–8.8), 2,3-dihydro-3-hydroxypapuanic acid (–8.3), (-)-papuanic acid (–8.5), (-)-isocalolongic acid (–8.9), isopapuanic acid (–8.1), isocalopolyanic acid (–8.8), glyasperin A (–10.8), broussoflavonol F (–9.9), (2S)-5,7-dihydroxy-40-methoxy-8-prenylflavanone (–9.3), isorhamnetin (–9.2), (1S)-2-trans, 4-trans-abscisic acid (–7.3), and (1S)-2-cis, 4-trans-abscisic acid (–7.2) Glyasperin A had the highest binding affinity compared to the other 12 compounds, which was higher than MLN-4760. Main protease Dewi et al [26] Native ligand (N3): –8.4 Sulabiroins A (–8.1), sulabiroins B (–7.8), 2',3'-dihydro-3'-hydroxypapuanic acid (–7.1), (-)-papuanic acid (–7.4), (–)-isocalolongic acid (–7.2), isopapuanic acid (–7.0), isocalopolyanic acid (–6.4), glyasperin A (–7.8), broussoflavonol F (–7.9), (2S)-5,7-dihydroxy-4'-methoxy-8-prenylflavanone (–7.9), isorhamnetinb (–7.3), (1'S)-2-trans,4-trans-abscisic acid (–6.5), (1'S)-2-cis,4-trans-abscisic acid (–6.0), curcumene (–5.5), thymol (–4.7), tetralin (–4.7), P-coumaric acid (–5.1), α-tocopherol succinate (–6.2), deoksi podophyllotoxin (–7.4), and xanthoxyletin (–6.7) Sulabiroins A had the highest binding affinity compared to the other 19 compounds, which was lower than native ligand (N3). Elwakil et al [16] Lopinavir: –8.18 Acid: n-hexadecanoic acid (–6.28), benzoic acid (–3.70), trans-caffeic acid (–4.48), tetradecanoic acid (–5.84), and trans-13-octadecenoic acid (–6.06) Octacosanol showed the highest binding affinity compared to the other 25 compounds, which was lower than lopinavir.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Khayrani et al [8] MLN-4760: –9.2 Sulabiroins A (–9.5), sulabiroins B (–8.8), 2,3-dihydro-3-hydroxypapuanic acid (–8.3), (-)-papuanic acid (–8.5), (-)-isocalolongic acid (–8.9), isopapuanic acid (–8.1), isocalopolyanic acid (–8.8), glyasperin A (–10.8), broussoflavonol F (–9.9), (2S)-5,7-dihydroxy-40-methoxy-8-prenylflavanone (–9.3), isorhamnetin (–9.2), (1S)-2-trans, 4-trans-abscisic acid (–7.3), and (1S)-2-cis, 4-trans-abscisic acid (–7.2) Glyasperin A had the highest binding affinity compared to the other 12 compounds, which was higher than MLN-4760. Main protease Dewi et al [26] Native ligand (N3): –8.4 Sulabiroins A (–8.1), sulabiroins B (–7.8), 2',3'-dihydro-3'-hydroxypapuanic acid (–7.1), (-)-papuanic acid (–7.4), (–)-isocalolongic acid (–7.2), isopapuanic acid (–7.0), isocalopolyanic acid (–6.4), glyasperin A (–7.8), broussoflavonol F (–7.9), (2S)-5,7-dihydroxy-4'-methoxy-8-prenylflavanone (–7.9), isorhamnetinb (–7.3), (1'S)-2-trans,4-trans-abscisic acid (–6.5), (1'S)-2-cis,4-trans-abscisic acid (–6.0), curcumene (–5.5), thymol (–4.7), tetralin (–4.7), P-coumaric acid (–5.1), α-tocopherol succinate (–6.2), deoksi podophyllotoxin (–7.4), and xanthoxyletin (–6.7) Sulabiroins A had the highest binding affinity compared to the other 19 compounds, which was lower than native ligand (N3). Elwakil et al [16] Lopinavir: –8.18 Acid: n-hexadecanoic acid (–6.28), benzoic acid (–3.70), trans-caffeic acid (–4.48), tetradecanoic acid (–5.84), and trans-13-octadecenoic acid (–6.06) Octacosanol showed the highest binding affinity compared to the other 25 compounds, which was lower than lopinavir.…”
Section: Resultsmentioning
confidence: 99%
“…A total of six in silico studies were conducted using the SARS-CoV-2 main protease enzyme as the target enzyme [16,25 − 29]. Several compounds from propolis had high binding affinity to the SARS-CoV-2 main protease enzyme, including octacosane ( − 7.39 kcal/mol) [16] , 3′-methoxydaidzin ( − 7.7 kcal/mol) [25] , sulabiroins A ( − 8.1 kcal/mol) [26] , rutin ( − 92.8 kcal/mol) [27] , glyasperin A ( − 7.8 kcal/mol) [28] , broussoflavonol F ( − 7.8 kcal/mol) [28] , and kaempferol ( − 7.8 kcal/mol) [29] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, protein structure was added by hydrogen polar as preparation for further analysis. The MLN-4760 and sulabiroins A were selected as control for the analysis [8].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Refaat et al (2021) demonstrated that propolis delivered in a liposomal encapsulation was as effective as remdesivir in neutralizing SARS-CoV-2 in vitro [90]. Many computational and molecular docking studies suggest the efficacy of propolis and its phenolic components in interfering with many important proteins of the SARS-CoV-2, including proteases and the spike protein [91][92][93][94].…”
Section: Antiviral Propertiesof Propolismentioning
confidence: 99%
“…Caffeic acid phenethyl ester was also shown to interfere with the highly conserved residues (substrate-binding pocket) of M pro protein of SARS-Cov-2 [113]. In addition, molecular docking studies by Sahlan et al (2021) and Dewi et al (2021) demonstrated that Sulabiroins A, (2S)-5,7-dihydroxy-4 -methoxy-8-prenylflavanone acid, glyasperin A, and broussoflavonol F (propolis-derived compounds) could potentially bind to various residues of M pro catalytic sites and consequently inhibit the activity of the M pro protein of SARS-Cov-2 [93,94]. Kwon et al (2020) demonstrated that kaempferol and p-coumaric acid prevented the entry of human rhinovirus and also inhibited the viral replication in HeLa cells [112].…”
Section: Mechanisms Of Action Of Antiviral Properties Of Propolismentioning
confidence: 99%